A liquid medium annealing strategy for highly [041]/[141]-oriented planar antimony sulfide solar cells with 7.23% efficiency. (February 2023) - Yao, Li-Quan; Lin, Li-Mei; Huang, Zhi-Ping; Mao, Yu; Li, Hu; Lin, Wen-Wei; Chen, Shui-Yuan; Huang, Zhi-Gao; Li, Jian-Min; Chen, Gui-Lin
Abstract: Antimony sulfide (Sb2 S3 ) is regarded as one of candidate materials for tandem top cells with silicon based solar cells due to its non-toxicity, appropriate bandgap, high absorption coefficient and good stability. However, restricted by the difficulty of carrier transportation caused by unfavorable orientations of Sb2 S3, the power conversion efficiency ( PCE ) is still relatively low. In this work, a new annealing method, called liquid medium annealing (LMA), is developed to versatilely regulate the orientation of Sb2 S3 films by controlling the concentration of Se2 2- -OAm. Compared with conventional vapor-assisted annealing, a highly [041]/[141] oriented Sb2 S3 film with unique title angles can be skillfully prepared by LMA with top-down model, which facilitates the photo-induced carrier separation along (Sb4 S6 )n ribbon. Meanwhile, such a LMA tactic can effectively tailor the band alignment at back contact by raises the valence band maximum (VBM) of Sb2 S3, and then reducing hole collection barrier. Finally, a high PCE of 7.23% is achieved and considered the first echelon in planar Sb2 S3 solar cells. Graphical Abstract: Sb2 S3 is regarded as one of candidate materials for tandem top cells with silicon based solar cell, due to its non-toxicity, appropriate bandgap, high absorption coefficient and good stability. Here, a new annealing method, called liquid medium annealing (LMA), is developed to versatilely regulate the orientation of Sb2 S3 films by controlling the concentration of Se2 2- -OAm. And the device with highly [041]/[141] orientations of Sb2 S3 film delivers a power conversion efficiency ( PCE ) of 7.23%, which is among the highest efficiency of Sb2 S3 planar solar cells to date. ga1 Highlights: An impressive PCE of 7.23% is achieved by a novel liquid medium annealing (LMA) for planar Sb2 S3 solar cells. Orientations regulation of Sb2 S3 films can be realized by controlling the concentration of Se2 2- -OAm medium. (041)/(140) orientations with unique title angles of (Sb4 S6 )n ribbon enhance carrier transport and reduce shunt path. Recycling oleylamine for LMA can effectively reduce the process cost.